P2X7 in Cancer: From Molecular Mechanisms to Therapeutics - Lara, Romain; Adinolfi, Elena; Harwood, Catherine A.; Philpott, Mike; Barden, Julian A.; Di Virgilio, Francesco; McNulty, Shaun (Frontiers in Pharmacology, 2020)
P2X7 is a transmembrane receptor expressed in multiple cell types including neurons, dendritic cells, macrophages, monocytes, B and T cells where it can drive a wide range of physiological responses from pain transduction to immune response. Upon activation by its main ligand, extracellular ATP, P2X7 can form a nonselective channel for cations to enter the cell. Prolonged activation of P2X7, via high levels of extracellular ATP over an extended time period can lead to the formation of a macropore, leading to depolarization of the plasma membrane and ultimately to cell death. Thus, dependent on its activation state, P2X7 can either drive cell survival and proliferation, or induce cell death. In cancer, P2X7 has been shown to have a broad range of functions, including playing key roles in the development and spread of tumor cells. It is therefore unsurprising that P2X7 has been reported to be upregulated in several malignancies. Critically, ATP is present at high extracellular concentrations in the tumor microenvironment (TME) compared to levels observed in normal tissues. These high levels of ATP should present a survival challenge for cancer cells, potentially leading to constitutive receptor activation, prolonged macropore formation and ultimately to cell death. Therefore, to deliver the proven advantages for P2X7 in driving tumor survival and metastatic potential, the P2X7 macropore must be tightly controlled while retaining other functions. Studies have shown that commonly expressed P2X7 splice variants, distinct SNPs and post-translational receptor modifications can impair the capacity of P2X7 to open the macropore. These receptor modifications and potentially others may ultimately protect cancer cells from the negative consequences associated with constitutive activation of P2X7. Significantly, the effects of both P2X7 agonists and antagonists in preclinical tumor models of cancer demonstrate the potential for agents modifying P2X7 function, to provide innovative cancer therapies. This review summarizes recent advances in understanding of the structure and functions of P2X7 and how these impact P2X7 roles in cancer progression. We also review potential therapeutic approaches directed against P2X7.